Beyond icons
1 online resource.
Keywords: "This book is a collective reflection on the relationship between theory and methods, as practiced by American archaeologists of the Byzantine period in Greece, Turkey, Ukraine, and Egypt between the 1990s and 2020s. The eleven authors represent a generational voice that employed theory to redirect the established narratives of the golden age of Byzantine archaeology (1960s-1980s) that privileged art and religion. Beyond Icons: Theories and Methods in Byzantine Archaeology in North America originated in three conferences (2010, 2012, and 2013) organized by the Program of Byzantine Studies at Dumbarton Oaks in Washington, D.C. Acknowledging the role that Dumbarton Oaks played in the golden age of Byzantine archaeology, Program director Margaret Mullett designed these conferences as exercises in conceptualizing the field's future. The essays consider theories of fragments, methodologies in regional surface survey, stratigraphy, habitus, phenomenology, gender theory, craft, dreams, and sound. In doing so, they capture a moment in an ongoing pivot in the study of Byzantine archaeology and material culture and chart out future directions for the field. This book will appeal to scholars and students alike, as well as all those interested in Byzantine Studies, medieval archaeology (particularly of the eastern Mediterranean), and Byzantine material culture. It will also be of interest to anyone seeking to understand the emerging narrative of a global Middle Ages. The essays reflect the ways in which the study of Byzantine archaeology was shaped by the scholarship of those working in the United States and Canada"--